Islamic education values in groom’s traditional makeup Kebesaran Banten - Mutimmatul Faidah; Festiana, Ailsa; Muntazeri, Eliya Najma (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
Banten is the westernmost region of Java island that is famous for its religiosity and distinctive culture. This study aimed to describe the characteristics of the groom’s makeup for Kebesaran Banten (The Name of the Groom’s makeup) and reveal the value of Islamic education for the bride and groom. This qualitative study used Spradley’s ethnographic research approach. Data were collected using in-depth interviews, participant observation, and documentation. The results revealed that the groom of Kebesaran Banten had natural soft makeup encrusted with golden makutaraja (crown) and a necklace of jasmine on the chest. The clothes were made of red, green, or black velvet, decorated with the side cloth of the Banten Sultanate and a shoulder sash. The groom wore trousers and sandals of the same color. At the waist, a dagger and a short spear were tucked in with a jasmine flower garland. This make-up represented Islamic culture that combined Javanese Hindu, Chinese, and European cultures. The value of Islamic education was manifested in the values of faith, morals, physical, rationality, psychological, sexual, and social. This makeup could be developed as a medium for internalizing the value of Islamic education for brides in forming a happy family based on faith. Overall, this make-up depicts the husband's figure as a family leader who is faithful, visionary, hardworking, maintaining family honor, and full of love.